Does executive compensation affect firms' acquisition decisions? Evidence from China. Issue 5 (20th October 2021) - Jiang, Lin; Kling, Gerhard; Bo, Hong
ABSTRACT: Exploiting regulatory changes in China that govern the use of stock options, we investigate whether executive compensation affects acquisition decisions and post-acquisition performance from 2005 to 2014. We find that acquisitions are not driven by stock options. Managerial stock ownership promotes acquisitions at low levels of ownership – but leads to less frequent acquisitions at higher levels, implying a non-linear relationship. Similarly, we also find a non-linear impact of managerial stock ownership on long-term post-acquisition performance. However, neither stock options nor stock ownership determine short-term post-acquisition performance. Finally, state ownership has a significant impact on the compensation-acquisition relationship in that the above relationships only exist in private enterprises.